1991
DOI: 10.1039/c39910000156
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II)–tetraphenylporphyrin–pyridine complex fixed on a glassy carbon electrode and its prominent catalytic activity for reduction of carbon dioxide

Abstract: Cobalt(ii)-tetraphenylporphyrin (CoVpp)-fixed glassy carbon (GC) electrodes were prepared using 4-aminopyridine (pyNH2) in the form of Colltpp-pyNH-CO/GC, which were active for electroreduction of C 0 2 to CO at potentials 100 mV more positive than water-soluble Coil porphyrins, and the overall turnover number of Coiltpp for CO production exceeded 105.Metalloporphyrins have been reported to be active as catalysts in the electroreduction of C 0 2 in aqueous' and nonaqueous2 media. In aqueous media, water-solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 9 publications
2
40
0
Order By: Relevance
“…2,[4][5][6][7][8][9][10][11][12][13][14] Among such catalysts, cobalt porphyrin complexes are considered to be one of the promising candidates since it selectively reduces CO 2 to CO with relatively small overpotential in aqueous solutions. 15,16 Recently, drastic improvements in terms of stability in aqueous medium, high selectivity in CO 2 reduction, and low overpotential, have been achieved by the immobilization to the graphite electrode 9,[17][18][19][20] or by using as the building blocks of COF (covalent organic frame-works) 8 and MOF (metal organic frameworks). 11 To achieve further improvement, understanding of catalytic effects of cobalt porphyrin complexes is quite important and, therefore, analyses using electronic structure calculations have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…2,[4][5][6][7][8][9][10][11][12][13][14] Among such catalysts, cobalt porphyrin complexes are considered to be one of the promising candidates since it selectively reduces CO 2 to CO with relatively small overpotential in aqueous solutions. 15,16 Recently, drastic improvements in terms of stability in aqueous medium, high selectivity in CO 2 reduction, and low overpotential, have been achieved by the immobilization to the graphite electrode 9,[17][18][19][20] or by using as the building blocks of COF (covalent organic frame-works) 8 and MOF (metal organic frameworks). 11 To achieve further improvement, understanding of catalytic effects of cobalt porphyrin complexes is quite important and, therefore, analyses using electronic structure calculations have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] To improve the catalyst'sd ispersion, strengthening the interaction between the molecular catalysts and supports as ameans to overcome self-stacking is necessary. [19,22,23] Another approach is to directly graft molecular catalysts onto the conductive substrates via covalent bonding.Y ao et al covalently linked ac obalt porphyrin complex with peripheral acetylene groups to ad iamond surface decorated with alkyl azides by azidealkyne cycloaddition. [19,22,23] Another approach is to directly graft molecular catalysts onto the conductive substrates via covalent bonding.Y ao et al covalently linked ac obalt porphyrin complex with peripheral acetylene groups to ad iamond surface decorated with alkyl azides by azidealkyne cycloaddition.…”
mentioning
confidence: 99%
“…[16] This can be realized by coordination of the metal centers and pyridine groups to the support. [19,22,23] Another approach is to directly graft molecular catalysts onto the conductive substrates via covalent bonding.Y ao et al covalently linked ac obalt porphyrin complex with peripheral acetylene groups to ad iamond surface decorated with alkyl azides by azidealkyne cycloaddition. [24] Maurin et al successfully modified carbon nanotubes by attaching Fe-porphyrin through acovalent bond between the peripheral carboxylic acid group and the surface amine group,obtaining ahigh CO selectivity and aturnover at 500 mV overpotential.…”
mentioning
confidence: 99%
“…Fujita et al later reported that iron(IV) and cobalt(III) corrole complexes similarly catalyze the reduction of CO2 to CO at −1.7 V vs. SCE under homogeneous conditions (Scheme 5) [60,61]. Cobalt porphyrin (CoTPP) and phtalocyanine (CoPc) complexes were also found to be catalytically active in water on carbon electrodes film-coated with the complexes [24,[62][63][64][65]. By using the Co(TPP) (Scheme 6) deposited on a carbon black gas-diffusion electrode, CO is produced at −0.76 V vs. SHE (overpotential = 230 mV) at 97% FE in a 0.5 M KHCO3 solution under a high CO2 pressure Cobalt porphyrin (CoTPP) and phtalocyanine (CoPc) complexes were also found to be catalytically active in water on carbon electrodes film-coated with the complexes [24,[62][63][64][65].…”
Section: Scheme 2 Structures Of Co and Ni Tetraaza Macrocyclic Complmentioning
confidence: 99%
“…Cobalt porphyrin (CoTPP) and phtalocyanine (CoPc) complexes were also found to be catalytically active in water on carbon electrodes film-coated with the complexes [24,[62][63][64][65]. By using the Co(TPP) (Scheme 6) deposited on a carbon black gas-diffusion electrode, CO is produced at −0.76 V vs. SHE (overpotential = 230 mV) at 97% FE in a 0.5 M KHCO3 solution under a high CO2 pressure Cobalt porphyrin (CoTPP) and phtalocyanine (CoPc) complexes were also found to be catalytically active in water on carbon electrodes film-coated with the complexes [24,[62][63][64][65]. By using the Co(TPP) (Scheme 6) deposited on a carbon black gas-diffusion electrode, CO is produced at −0.76 V vs. SHE (overpotential = 230 mV) at 97% FE in a 0.5 M KHCO 3 solution under a high CO 2 pressure of 20 atm.…”
Section: Scheme 2 Structures Of Co and Ni Tetraaza Macrocyclic Complmentioning
confidence: 99%